Trades & the norms to design curricula for the training of handicapped lepers - Do, Mạnh Cường (Journal of Technical Education Science, 2010)
In our two previous articles (Journal of Technical Education Science, no. 14), we have presented some of the handicapped lepers’ characteristics and some models for the curriculum design in the training of handicapped lepers. In this article, we introduce some norms to select and design training programs for them.